High prevalence of vitamin D insufficiency and its association with BMI-for-age among primary school children in Kuala Lumpur, Malaysia - Khor, Geok Lin; Chee, Winnie S S; Mohd Shariff, Zalilah; Poh, Bee K; Arumugam, Mohan; Ab Rahman, Jamalludin; Theobald, Hannah E (BioMed Central, 2011)
Background Deficiencies of micronutrients can affect the growth and development of children. There is increasing evidence of vitamin D deficiency world-wide resulting in nutritional rickets in children and osteoporosis in adulthood. Data on the micronutrient status of children in Malaysia is limited. The aim of this study was to determine the anthropometric and micronutrient status of primary school children in the capital city of Kuala Lumpur.